(3QSGdI GdaUOs - (3bSWG Hf dhbG GdHYdHcj,J (B300 (3g` s
(3ChdgG (B:s
(3bGd bSWG Hf dhbG GLgGO GdfaS (B/ (3GdhbG HGdaQGjV aCdaJ dc CYRc Gddg cJGHkG LeYJ ajg eG PcQfG LGdjfhS fe GdYdGL HGdaUO s
(3BNQgG (B:s
(3jfHZi Cf jchf GHJOGA YdGLg HGdaUO aEf cGfJ GdeGOI Zdi XGgQ GdLdO adjS jfHZi Cf jJhba YdGLg Edi Cf jXgQ JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdQGHYIs
(3Je cJGHI gPg GdfSNI ef fSNI SbjeIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B131s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(568) s
Keywords: (3GdWHs